Decision Support System For Selecting Bali Tourist Attractions Using The PROMETHEE Method - Zuraidah, Eva (Politeknik Ganesha Medan, 2019)
Tourism is currently very potential to be developed as a source of local income by providing information both online and offline to the community so that regional income increases. Bali is one of the tourist destinations in Indonesia which is visited by many local and foreign tourists. The island of Bali has many interesting sights consisting of natural attractions, royal festivals, culinary tours, traditional markets, and museums. There are many criteria that must be considered, so through this recommendation system, tourists can find out what places are in Bali they will visit. One of the problems of decision making with many criteria and attributes in the selection of attractions is to provide detailed decisions that refer to the scale of weight possessed. Decision support systems provide priority results of attractions that are suitable for every traveler. Traveling is very important because with tourism we can eliminate fatigue due to activity during the day. The selection of the right tourist attraction also affects this, so it is necessary to choose the right tourist attraction. This study focused on the application of multi-attribute decision making (MADM) to decision support systems (SPK) using preferred organizational methods for enrichment and evaluation (Promeethe). When a traveler fills out a questionnaire, he must be consistent with the answers to get the best results based on his willingness and characteristics. This research uses descriptive analysis method that presents a summary of the results of surveys and interviews of tourists who want to choose Bali tourist attractions according to costs, security, natural beauty, facilities, and infrastructure and location.